MAGNETIC RESONANCE IMAGING OF PERIANAL FISTULA: EVALUATING THE SENSITIVITY AND SPECIFICITY OF STIR (SHORT TAU INVERSION RECOVERY) & DWI (DIFFUSION WEIGHTED IMAGING) (The Research of Medical Science Review, 2025)
Background: Perianal fistulas are abnormal tracts commonly caused by chronic inflammation or infection, requiring precise imaging for diagnosis and treatment planning. MRI is the gold standard for evaluating fistulas, offering excellent soft tissue contrast and detailed visualization of tracts and abscesses. STIR and DWI sequences enhance the detection of inflammation and restricted diffusion, critical for identifying active disease. This study aims to evaluate the sensitivity and specificity of these sequences in diagnosing perianal fistulas. Objective: To evaluate the sensitivity and specificity of STIR (short tau inversion recovery) & DWI (diffusion weighted imaging) of magnetic resonance imaging for diagnosis of perianal fistula. Methodology: The research was conducted at Chughtai Diagnostic Center, Gujranwala, involving patients with perianal fistulas. Data collection from STIR, DWI-MRI was conducted after obtaining informed consent. Results: The study included 51 patients, 9 (17.6%) were females 42 (82.4%) were males with a mean age of 37 years (range: 18–56years). Pus discharge was observed in 80.4% of cases, with detection rates of 82.4% on DWI and 58.8% on STIR. Fistula locations were classified as intersphincteric (41.2%), transphincteric (27.5%), suprasphincteric (19.6%), and extrasphincteric (11.8%). Abscesses were detected in 82.4% on DWI and 58.8% on STIR (moderate agreement, Kappa = 0.469). DWI identified more simple tracts (33.3%) than STIR (15.7%) (Kappa = 0.542). DWI had higher sensitivity for detecting edema (96.77%), abscesses (71.4%), and fibrotic changes (96.66%). Conclusion: The study concluded that the advanced imaging techniques, particularly DWI, play a crucial role in the diagnosis of perianal fistulas. The study found that DWI is highly effective for detecting edema and fibrotic changes, with high sensitivity for edema detection. While the agreement between DWI and STIR imaging was variable, DWI showed a strong diagnostic capability, particularly for assessing perianal abnormalities such as fibrotic changes and edema. The results suggest that DWI could be a valuable tool in improving the accuracy of perianal fistula diagnosis, with the potential to guide treatment planning and enhance the understanding of disease characteristics.